1999
DOI: 10.1007/s002130051171
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2D6 genotype and steady state plasma levels of risperidone and 9-hydroxyrisperidone

Abstract: The role of the polymorphic cytochrome P450 2D6 (CYP2D6) in the metabolism of risperidone to its major active metabolite, 9-hydroxyrisperidone (9-OH-risperidone), has been documented after single oral doses of the drug. In this study, the influence of the CYP2D6 polymorphism on the steady-state plasma concentrations of risperidone and 9-OH-risperidone was investigated. Thirty-seven schizophrenic patients on monotherapy with risperidone, 4-8 mg/day, were genotyped by RFLP and PCR for the major functional varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(110 citation statements)
references
References 29 publications
8
99
1
2
Order By: Relevance
“…14 In this study, a new CYP2D6 allele (*58 allele) was identified as a result of the current testing efforts (GenBank accession #DQ282162). Whereas the poor metabolism phenotype in African-Americans is estimated to be only 2% based on currently confirmed null CYP2D6 alleles evaluated, 19 in vivo CYP2D6 activity measurements suggest that the frequency for poor metabolism in African-Americans may be closer to 7%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…14 In this study, a new CYP2D6 allele (*58 allele) was identified as a result of the current testing efforts (GenBank accession #DQ282162). Whereas the poor metabolism phenotype in African-Americans is estimated to be only 2% based on currently confirmed null CYP2D6 alleles evaluated, 19 in vivo CYP2D6 activity measurements suggest that the frequency for poor metabolism in African-Americans may be closer to 7%.…”
Section: Discussionmentioning
confidence: 96%
“…37 The risperidone/9-OH ratio in patient plasma is dependent on CYP2D6 activity as 9-OH risperidone is formed by CYP2D6 metabolism of risperidone. 19,[38][39][40] It was notable that this ratio was not increased by the expression of the CYP2D6*17 allele in African-Americans (as would be expected for a CYP2D6 allele resulting in reduced activity), but rather decreased (Figure 1). This suggests the CYP2D6*17 allele may facilitate risperidone metabolism rather than diminish its metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In the liver, risperidone is extensively metabolized by CYP2D6 to the active metabolite 9-OH-risperidone. 11 The CYP2D6 gene is extremely polymorphic and its variants are classified, based on encoded protein activity level, into four different phenotypes, which have a profound influence in the outcome of drug therapy: (1) extensive metabolizers, carry one or two alleles with normal function; (2) intermediate metabolizers, carry two decreased-function alleles or are heterozygous for one deficient allele and one decreased-function allele; (3) poor metabolizers, carry two non-functional alleles; (4) ultrarapid metabolizers, carry multiple copies of functional alleles. 12 In the brain, risperidone binds multiple neurotransmitter receptors, with stronger affinity to the serotonin 2A (5-HT2A) and dopamine D2 receptors, and a good affinity for the a-1 and a-2C adrenergic receptors and for the serotonin receptors 6 and 7 (5-HT6 and 5-HT7).…”
Section: Introductionmentioning
confidence: 99%
“…According to in vivo and in vitro studies, cytochrome P450 (CYP) enzymes CYP2D6 and, to a lesser extent, CYP3A4 are responsible for the 9-hydroxylation of risperidone [4][5][6][7]. As 9-OH-risperidone is approximately equipotent with the parent drug in terms of dopamine receptor affinity, the total risperidone active moiety (risperidone plus 9-OH-risperidone) is regarded to contribute to the overall antipsychotic effect [8].…”
Section: Introductionmentioning
confidence: 99%